A functional dominant mutation in Schizosaccharomyces pombe RNase MRP RNA affects nuclear RNA processing and requires the mitochondrial-associated nuclear mutation ptp1-1 for viability. - Paluh, J L (1996)
The essential gene for RNase MRP RNA, mrp1, was identified previously in Schizosaccharomyces pombe by homology to mammalian RNase MRP RNAs. Here we describe distinct site-specific mutations in RNase MRP RNA that support a conserved role for this ribonucleoprotein in nucleolar 5.8S rRNA processing. One characterized mutation, mrp1-ND90, displays dominance and results in accumulation of unspliced precursor RNAs of dimeric tRNA(Ser)-tRNA(Met)i, suggesting a novel nuclear role for RNase MRP in tRNA processing. Cells carrying the mrp1-ND90 mutation, in the absence of a wild-type copy of mrp1, additionally require the mitochondrially associated nuclear mutation ptp1-1 for viability. Analysis of this mrp1 mutation reinforces previous biochemical evidence suggesting a role for RNase MRP in mitochondrial DNA replication. Several mutations in mrp1 result in unusual cellular morphology, including alterated nuclear organization, and are consistent with a broader nuclear role for RNase MRP in regulating a nuclear signal for septation; these results are a further indication of the multifunctional nature of this ribonucleoprotein.